Documentary letters of credit - Griffiths, Nigel; Smith, Warren (London : Financial i Production, 1989)
This video consists of two videos. Explain on the credit cycle, special credits, the documents and discrepancies
Two videos in one container + three books of training guide
Sponsored by Lloyds Bank
Writer, Warren Smith
Keywords: Letters of credit